2020
DOI: 10.1111/cbdd.13610
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes from Poria cocos are revealed as potential retinoid X receptor selective agonists based on cell and in silico evidence

Abstract: Poria cocos is an edible and medicinal fungus that is widely used in Traditional Chinese Medicines as well as in modern applications. Retinoid X receptor (RXR) occupies a central place in nuclear receptor signaling, and a pharmacological RXRdependent pathway is involved in myeloid cell function. Here, structural information for 82 triterpenes from P. cocos and 17 known RXR agonists was collected in a compound library and retrieved for a molecular docking study. Three triterpenes, 16α-hydroxytrametenolic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Prior to molecular docking, the crystal structure of the ligand-binding domain of GR (Protein Data Bank (PDB) code: 1NHZ) was downloaded as previously described. 29 The initial setup of the GR structure for docking was performed using the Protein Preparation Wizard module in Maestro (Schrodinger, LLC). 30 The grid was sized to 20 Å in each direction at the center of the binding pocket.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to molecular docking, the crystal structure of the ligand-binding domain of GR (Protein Data Bank (PDB) code: 1NHZ) was downloaded as previously described. 29 The initial setup of the GR structure for docking was performed using the Protein Preparation Wizard module in Maestro (Schrodinger, LLC). 30 The grid was sized to 20 Å in each direction at the center of the binding pocket.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Cells were maintained in basic Dulbecco's modified Eagle's medium as described. 29 Cell Viability. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was employed to detect the cytotoxicity of triterpenoids from P. cocos on Caco-2, 293T, and RAW 264.7 cells, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it can also inhibit tumour growth and exert antitumour effects by enhancing the body's immune function. Triterpenes and polysaccharide compounds are the main active components of PRP (Xu et al, 2020;Yi et al, 2020). Studies have shown that triterpenes (poria cocoic acid) can inhibit the secretion of IL-2 and IFN-γ and affect the killing of target cells by cytotoxic T cells and the apoptosis of cardiomyocytes (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%